Correction: Modeling multi-sensory feedback control of zebrafish in a flow. - Daniel A Burbano-L; Maurizio Porfiri (PLoS Computational Biology, 2022)
[This corrects the article DOI: 10.1371/journal.pcbi.1008644.].